Analisis Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah (Dprd) Di Kabupaten Siak Dalam Perspektif Undang-Undang Nomor 23 Tahun 2014 Tentang Pemerintahan Daerah - Handi, Dian Mega; Zulwisman, Zulwisman; HB, Gusliana (Peneliti.net, 2024)
The function of the DPRD regarding authority in terms of supervision over the implementation of Regional Regulations is also regulated in Article 101 Paragraph (1) C of Law Number 9 concerning the second amendment to Law Number 23 of 2014 which reads: